Art flippers - Brytpunkten mellan de gamla och de nya spelreglerna på konstmarknaden - Norberg,Stina (2015)
A change is happening on today’s art market. Technological and digital developments have led to new concepts and social structures. These have changed the way the art market works and how it is constructed. The digital era has opened up many possibilites for the artists, the art dealers and for persons with interest in investing in unestablished artists and contemporary art. The theory in this bachelor thesis is about the regulations on the art market and where the change from the old regulations to the new ones emerge. In this paper I am referring to these regulations as ”game rules” of the art market. I have also studied how commercial interests on the international art market affects the artist and the art. New concepts has arisen from the development such as art flipper, a concept that I am going to study close up in this essay. Art flippers is a new type of art dealer that buy new, unestablished art from young artists and then sells it with profit. My method will consist of a content analysis based on articles and printed literature. The result of this study is that the digitization of society enables and reveals a shift in the art market as well as a distinction between the old and the new game rules.
Keywords: värde; ekonomi; art flipper; konstmarknad; spelregler; rykte; konstvärld; economy; art worlds; art markets art game rules